Proximal Disinsertion of the Common Extensor Tendon for Lateral Elbow Tendinopathy. (April 2013) - Cusco, Xavier; Alsina, Montserrat; Seijas, Roberto; Ares, Oscar; Alvarez-Diaz, Pedro; Cugat, Ramon
Purpose: To evaluate surgical outcomes of disinsertion of the common extensor tendon for lateral elbow tendinopathy. Methods: Records of 277 men and 128 women who underwent surgery for lateral elbow tendinopathy were reviewed. The indication for surgery was insufficient improvement of pain and inability to return to work after 3 weeks of physiotherapy (stretching, ultrasound) and local corticosteroid injections. According to the Tavernier technique, the origin of the tendons of the extensor carpi radialis brevis and extensor digitorum communis was located, and proximal disinsertion of the common extensor tendon was performed. Results: Outcome was excellent in 344 (85%) of the patients, good in 46 (11.5%), regular in 9 (2%), and poor in 2 (0.5%). The mean time to return to work was 29 (range, 5–93) days. Immediate complications included infection (n=1), seroma (n=1), cicatricial fibrosis (n=10), radial neuritis (sensory) [n=4], and reactive dermatitis (n=2). Late complications included Frohse's arcade syndrome (n=1) and carpal tunnel syndrome (n=2). Conclusion: Disinsertion of the proximal common tendon is a good option for treating lateral elbow tendinopathy.